Teacher Satisfaction in Relationships With Students and Parents and Burnout - Pedditzi, Maria Luisa; Nonnis, Marcello; Nicotra, Eraldo Francesco (Frontiers in Psychology, 2021)
In the educational field, the role of the support component of the teacher-student relationship is well known, while the role of the teacher-student relationship on teacher burnout is a more current field of investigation. Several studies on the sources of burnout have recently focused on job satisfaction and teacher-student satisfaction. However, the role of teacher-parent satisfaction is still little explored in this field. Moreover, in the Italian school context, students’ seniority and educational level require further investigation, as the average age of teachers is particularly high compared to their European colleagues. The present study aims to examine in a sample of 882 Italian teachers the presence of burnout and differences in teacher-student and teacher-parent satisfaction between primary (students aged 6–10 years) and lower secondary (students aged 11–13 years) teachers. A further objective is to test whether teacher-student and teacher-parent satisfaction and seniority can be significant predictors of burnout. Teachers completed the Job Satisfaction Scale (MESI) and the MBI- Educators Survey and the data were then processed using MANOVA and multiple linear regression analysis. The results revealed that 8.2% of the teachers suffered from burnout and lower secondary teachers showed the highest levels of emotional exhaustion, depersonalisation and reduced personal accomplishment. Predictors of emotional exhaustion were job dissatisfaction and seniority, and predictors of depersonalisation were job dissatisfaction and teacher-student dissatisfaction. Finally, predictors of personal accomplishment were also teacher-parent satisfaction and teacher-student satisfaction. The implications of these findings for practice and research are discussed in this article.